Sulcosticta fliedneri sp. nov. (Odonata: Platystictidae), a new damselfly from Luzon, Philippines - Phan, Quoc Toan; Keetapithchayakul, Tosaphol Saetung; Digma, Jonathan Rodrin (Zootaxa, 2025)
Sulcosticta fliedneri sp. nov. (holotype ♂, 15.25326° N, 121.39115° E, 65 m a.s.l., Dingalan, Aurora, Luzon, deposited at Cavite State University, Philippines) is described from Luzon Island based on specimens of both sexes. The new species is diagnosed by the distinctive morphology of the male’s anal appendages: cerci robust with a small distal tubercle and paraprocts black, acutely curved at the tip.